Implementasi Gaya Kepemimpinan Transformasional di Pondok Darut Tauhid Pesantren Zainul Hasan Genggong Probolinggo - Nurhidayah, Wulan; Izzah, Ismatul; Rachman, Poppy (CV. Creative Tugu Pena, 2024)
This research aims to explore the implementation of Transformational Leadership Style in Pondok Darut Tauhid by utilizing all aspects of life in the pesantren. The research method used in this research is descriptive qualitative with data collection techniques used, namely documentation, interviews and observations. The results of this study indicate that transformational leadership in Darut Tauhid boarding school must be based on several principles, namely: First Idealized Influence where the leader is able to influence all human resources within the scope of the pesantren, Second Inspirational Motivation is shown by the ability to motivate students and asatidz in carrying out responsibilities. Third, Innovation is a change that continues and will continue to be made towards something better. Fourth, Pioneer as a figure who is able to take risks on things that do not yet exist within the scope of the pesantren. Keywords: Transformational Leadership, Islamic Boarding School.